Study on antibacterial effect of halicin (SU3327) against Enterococcus faecalis and Enterococcus faecium. Issue 1 (24th September 2022) - Hussain, Zubair; Pengfei, She; Yimin, Li; Shasha, Liu; Zehao, Li; Yifan, Yang; Linhui, Li; Linying, Zhou; Yong, Wu
Abstract: Enterococci are important pathogens of nosocomial infections and are increasingly difficult to treat due to their intrinsic and acquired resistance to a range of antibiotics. Therefore, there is an urgent need to develop novel antibacterial agents, while drug repurposing is a promising approach to address this issue. Our study aimed to determine the antimicrobial efficacy of halicin against enterococci and found that the minimum inhibitory concentrations (MIC) of halicin against different strains of Enterococcus faecalis and Enterococcus faecium ranged from 4 to 8 μg/ml. In addition, the synergistic antibacterial effect between halicin and doxycycline (DOX) against Enterococcus was observed through the checkerboard method, and it was observed that halicin and DOX could significantly synergistically inhibit biofilm formation and eradicate preformed biofilms at sub-MICs. Moreover, the electron microscope results revealed that halicin could also disrupt the bacterial cell membrane at high concentrations. Furthermore, it is also confirmed that the combination of halicin and DOX has no significant cytotoxic effect on erythrocytes and other human-derived cells. In addition, the mouse subcutaneous model and H&E staining showed that the combination of halicin and DOX could effectively reduce the bacterial load and inflammatory infiltration without obvious side effects. In nutshell, these results demonstrate the potential of halicin in combination with DOX as a novel therapy against infections by Enterococcus. Abstract : This study demonstrates the potential of halicin in combination with DOX as a novel therapy against infections by Enterococcus.